2007
DOI: 10.1002/pola.22144
|View full text |Cite
|
Sign up to set email alerts
|

Electrosyntheses of high‐quality polyphenanthrene in the electrolyte of boron trifluoride diethyl etherate containing trifluoroacetic acid

Abstract: A novel inherently conducting polymer, high‐quality polyphenanthrene (PPh) films were synthesized electrochemically by direct anodic oxidation of phenanthrene (Ph) in boron trifluoride diethyl etherate (BFEE) containing a certain amount of trifluoroacetic acid (TFA). The oxidation potential of Ph in this medium was measured to be only 0.63 V versus SCE, which was greatly lower than that determined in acetonitrile + 0.1 mol L−1 Bu4NBF4 (1.55 V vs. SCE). The electrolytes of BFEE containing TFA enable facile anod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…This may imply an ordered graph-A C H T U N G T R E N N U N G itization of the residual char. In particular, the char yields of 73.5 % at 1000 8C and 70.6 % at 1300 8C are much higher than those of some carbon precursors like polyfluoranthene (24 % at 855 8C), [30] viscose rayon (28.5 % at 950 8C), [31] polyacrylonitrile (50 % at 900 8C), [32] polyphenanthrene (65 % at 907 8C), [29] poly (9,10-anthracenediylidene) (70 % at 900 8C), [33] and modified pitch (72 % at 1000 8C), [34] and are even very close to that of typically high char-yield mesophase pitch (75 % at 1000 8C). [34] Moreover, the char formed at 1000 8C consists of fine carbon microparticles with an average particle size of 118 mm (Figure 10 c), a size-polydispersity index of 1.08, and high conductivity of 2.1 S cm…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This may imply an ordered graph-A C H T U N G T R E N N U N G itization of the residual char. In particular, the char yields of 73.5 % at 1000 8C and 70.6 % at 1300 8C are much higher than those of some carbon precursors like polyfluoranthene (24 % at 855 8C), [30] viscose rayon (28.5 % at 950 8C), [31] polyacrylonitrile (50 % at 900 8C), [32] polyphenanthrene (65 % at 907 8C), [29] poly (9,10-anthracenediylidene) (70 % at 900 8C), [33] and modified pitch (72 % at 1000 8C), [34] and are even very close to that of typically high char-yield mesophase pitch (75 % at 1000 8C). [34] Moreover, the char formed at 1000 8C consists of fine carbon microparticles with an average particle size of 118 mm (Figure 10 c), a size-polydispersity index of 1.08, and high conductivity of 2.1 S cm…”
mentioning
confidence: 98%
“…Compared to the spectrum of pyrene monomer, the resonance peaks of the polypyrene significantly extend over a wider range of chemical shifts and also become broad because of the establishment of the long pconjugated structure in polypyrene chains. [29] All the proton resonance peaks in the COSY and HSQC spectra are indicated in the high-resolution 1 H NMR spectrum in Figure 5. Note that two pairs of cross-peaks [(e8.33, 126.2) and (g8.36, 128.9)] in Figure 7 a are stronger than the others, that is, the 2,7-pyrenylene units in the polypyrene are more numerous than the others, which is basically verified by Figure 5; in other words, the polypyrene chains may consist of more 2,7-pyrenylene units and fewer 1,6-/1,3-pyrenylene units.…”
mentioning
confidence: 99%
“…Some new peaks appeared after polymerization, and most of the peaks moved to a lower field, which was mainly because of the introduction of a higher conjugation length in the PPh main chain. As shown in Figure 6(B), the proton chemical shift from about 8.85 to 9.17 was ascribed to the protons at C (4) and C (5) , and the proton chemical shift from about 7.80 to 8.00 was ascribed to the protons at C (1) , C (3) , C (6) , and C (8) (Scheme 1). The origin of the peak at about 7.20 was attributed to the terminal proton in the polymer because of its small shift in field relative to those of the peaks of monomer [C (2) and C (7) ].…”
Section: Structural Characterizationsmentioning
confidence: 94%
“…3 Polyphenanthrene, representing the simplest tricyclic aromatic hydrocarbons, has been studied theoretically because of its great technological importance as an electrode material for lithium-ion rechargeable batteries. 4,5 However, to date, there have only been a few publications 8,9 concerned with polymers prepared from 9,10-dihydrophenanthrene (Ph; Scheme 1) with an ethylene-type bridge in the poly(para-phenylene). At the very start, Saito et al 8 reported the preparation of poly(9,10-dihydrophenanthrene) (PPh) obtained from 2,7-dibromo-9,10-dihydrophenanthene with an isolated zero-valent nickel complex and an electrochemically generated zero-valent nickel complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation